Synchronisation of data transfer in cloud. (1st January 2014) - Kundu, Anirban; Luan, Lin; Liu, Ruopeng
This paper proposes synchronised data transfer between different clusters of a cloud system network. It is configured for high-performance, scalable, multidirectional asynchronous file replication and synchronisation. Our design overcomes performance and scalability shortcomings of conventional synchronisation tools in runtime for maximum speed utilisation with replication and synchronisation over LANs and WANs. Cloud server-side environment is going to be proposed as network structure having distinct levels for controlling data transfer in different segments based on user/system requirements forming specified and dedicated channels. Serial and parallel executions demonstrate within paper in respect of number of computations and time consumption. Dynamic scheduler and node status controller are to be exploited to have better synchronisation. Theory on minimum criteria of network partition based on number of paths available for transmission of data from one network to another is going to be established. Experimental results demonstrate TCP connections and real-time activities between modules in cloud.